Whitening Efficiency of Laser 940 nm and LED (450-505) nm on Extrinsic Stained Teeth (in vitro study) - Ali A Hassab; Basima Mohammed Ali Hussein; Mohammed G Rzoqi G Rzoqi (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Teeth staining is one of the esthetic problems faced by dentists and patients. Many methodshave been suggested as crowns, restorations and bleaching. Dental bleaching effectiveness depends on manyfactors including technique and materials.Objectives: Studying the effect of diode laser 940 nm and light emitting diode (450-505) nm in bleaching ofstained teeth regarding : whitening efficiency; pulp temperature; surface roughness and topography.Materials and Methods: 40 extracted anterior teeth divided into 6 groups immersed at 37 oC in eithertea; coffee; cola ; juice for 14 days, tobacco stained teeth as well as control group were also included (immersed in distilled water ). These groups were subdivided into laser group or light emitting diode groupbleached according to manufacturer specifications. Shades of teeth were recorded before and after bleaching.Furthermore, temperature changes during bleaching were recorded using thermocouple Thermometer. Allspecimens were examined under light microscope, Atomic Force Microscope and Sectioning ElectronicMicroscope to study the surface roughness and topography.Results: the light emitting diode group yielded slight significant whitening efficiency with more pulptemperature rise (3.4 ºC) compared to the laser group (1.4 ºC). Both groups showed non-significant effect onroughness and topography compared to control group.Conclusion: Although light emitting diode group showed slightly significant shade improvement, but theincrease in pulp temperature was greater than that of laser group indicated better prognosis and safety whendiode laser 940 nm used. Conducting between efficiency and preservation, diode laser is superior in safetyand slightly similar whitening efficiency.